SASSY: A Framework for Self-Architecting Service-Oriented Systems - Menasce, D.; Gomaa, H.; Malek, S.; Sousa, J. (IEEE software, 2011)
Making architectural decisions manually in the presence of quality-of-service trade-offs can be complicated. The SASSY (Self-architecting Software Systems) framework automatically generates candidate software architectures and selects the one that best serves stakeholder-defined, scenario-based quality-of-service (QoS) goals. This lets domain experts concentrate on functional and QoS requirements. SASSY reduces the effort of composing service-oriented systems by automatically generating the QoS-optimized architecture and rapidly reconfiguring it at runtime. Self-architecting occurs during initial system deployment and at runtime, thus making systems self-adaptive, self-healing, self-managing, and self-optimizing.